Treinamento muscular inspiratório em pacientes com doença do refluxo gastroesofágico - Barreto, Patriciane Hedwiges (2019)
INTRODUCTION: Gastroesophageal reflux represents a physiological event that consists of the return of the gastric contents to the esophagus, which can be considered Gastroesophageal Reflux Disease (GERD). OBJECTIVE: To evaluate the effect of inspiratory muscle training on esophageal sphincter pressure (LES) in individuals with Gastroesophageal Reflux Disease. METHODS: Study randomized study performed at the Walter Cantídio University Hospital (HUWC), with GERD patients. Participants were randomized and divided into two groups: no-load training group (TSC) and a load-training group (CBT) submitted to inspiratory muscle training (IMT) 3 times a week for 8 weeks. RESULTS: The sample composed of 32 volunteers allocated in the TSC groups formed by 15 volunteers, 5 men (33%) and 10 women 67%) with a mean age of 42.67 ± 11.06 group BMI was 27.89%; the CBT group composed of 17 volunteers, 6 men (32%) and 11 women (63%) with a mean age of 49.65 ± 7.65 years and the BMI of group was 28.47%. The CBT group showed a significant increase in MIP (p<0.016). CBT vs TSC in isolated symptoms of mid-chest burning (p <0.009) and chest pain (p<0.001) and CBT vs PRE in the symptoms of hoarseness (p = 0.0171), throat clearing (p = <,0001) and cough uncomfortable (p = 0.0069). Comparing all patients PRE vs POST, there was an increase intraesophageal pressure in normal breathing. CONCLUSION: IMT reduced symptoms of gastroesophageal reflux disease, significantly increased MIP and Significant increase in Intraesophageal Pressure was observed.